2020
DOI: 10.1177/2332858420901696
|View full text |Cite
|
Sign up to set email alerts
|

Do You Get the Picture? A Meta-Analysis of the Effect of Graphics on Reading Comprehension

Abstract: Although convergent research demonstrates that well-designed graphics can facilitate readers’ understanding of text, there are select situations where graphics have been shown to have no effect on learners’ overall text comprehension. Therefore, the current meta-analytic study examined 39 experimental studies published between 1985 and 2018 measuring graphics’ effects on readers’ comprehension. We first quantified the overall effect on reading comprehension. Then, we considered interactions with learners’ char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 75 publications
(138 reference statements)
0
21
0
1
Order By: Relevance
“…To put this multitasking effect in context, the effect size is similar to the overall negative effect of reading from screens compared with paper ( g = −0.25, Clinton, 2019; g = −0.21, Delgado et al, 2018; g = −0.21, Kong et al, 2018). Multitasking's effect is also smaller than the beneficial effect of graphics ( g = 0.39, Guo, Zhang, Wright, & McTigue, 2020). The comprehension performance of narrative texts has been found to be higher than that of expository in two meta‐analyses ( g = 0.36, Clinton et al, 2020; g = 0.55, Mar et al, 2021), and multitasking's effect is smaller than that of genre.…”
Section: Discussionmentioning
confidence: 99%
“…To put this multitasking effect in context, the effect size is similar to the overall negative effect of reading from screens compared with paper ( g = −0.25, Clinton, 2019; g = −0.21, Delgado et al, 2018; g = −0.21, Kong et al, 2018). Multitasking's effect is also smaller than the beneficial effect of graphics ( g = 0.39, Guo, Zhang, Wright, & McTigue, 2020). The comprehension performance of narrative texts has been found to be higher than that of expository in two meta‐analyses ( g = 0.36, Clinton et al, 2020; g = 0.55, Mar et al, 2021), and multitasking's effect is smaller than that of genre.…”
Section: Discussionmentioning
confidence: 99%
“…Pictorial questions were more likely to be answered correctly by participants in the repeatability study with evidence suggesting surveys and written text designed with visual aids are completed in less time and with greater participant comprehension [ 69 , 70 ]. A significant difference was detected in change of score for CVD risk factors between the two test periods.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily quantitative, many aforementioned studies focus on students' reading outcomes after studying a visual, such as how a diagram facilitated comprehension. A recent meta-analytic study (Guo, Zhang, McTigue, & Wright, 2017) revealed that the inclusion of visuals has an overall medium positive effect on students' reading comprehension, with an overall effect size of .49.…”
Section: How Do Visuals Affect Learning?mentioning
confidence: 99%